Spatial Virome Analysis of Zanthoxylum armatum Trees Affected With the Flower Yellowing Disease - Cao, Mengji; Zhang, Song; Liao, Ruiling; Wang, Xiaoru; Xuan, Zhiyou; Zhan, Binhui; Li, Zhiqi; Zhang, Jie; Du, Xinnian; Tang, Zhengsen; Li, Shifang; Zhou, Yan (Frontiers in Microbiology, 2021)
Zanthoxylum armatum is an important woody crop with multiple applications in pharmaceutics, cosmetics, and food industries. With continuous increases in the plantation area, integrated pest management is required for scale production when diseases caused by biotic factors such as pests and pathogens have become new problems, one of which is the infectious flower yellowing disease (FYD). Here, isolates of a new illarvirus (3) and a new nepovirus-associated subviral satellite RNA (12) were identified in Z. armatum, in addition to 38 new isolates of four previously reported RNA viruses. Sequence variation can be observed in viral/subviral quasispecies and among predominant isolates from the same or different samples and geographic origins. Intriguingly, RNA sequencing of different diseased trees invariably showed an extraordinary pattern of particularly high reads accumulation of the green Sichuan pepper-nepovirus (GSPNeV) and the satellite RNA in symptomatic tissues. In addition, we also examined small RNAs of the satellite RNA, which show similar patterns to those of coinfecting viruses. This study provides further evidence to support association of the FYD with viral/subviral infections and deepens our understanding of the diversity and molecular characteristics of the viruses and satellite, as well as their interactions with the host.